2000
DOI: 10.1002/1097-0215(20001015)88:2<191::aid-ijc7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

p53-dependent induction of heat shock protein 27 (HSP27) expression

Abstract: Transcriptional activation of the p53 target genes plays a critical role in the cellular response to DNA damage, hypoxia, cellular stress and other signals regulating the cell cycle and apoptosis. The discovery of new p53 target genes continues to reveal novel mechanisms of action of this multifaceted protein. We used cDNA arrays to search for p53‐regulated genes in prostate cancer cells. In this report, we describe robust induction of heat shock protein 27 (hsp27) in prostate cancer cells (DU145, LNCaP, PC3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The Hsp27 protein, which lies downstream of p38MAPK, is a member of the heat-shock class of proteins which play pivotal roles in a variety of cellular processes such as stress and apoptosis. Hsp27 is of particular interest to our laboratory because it has been described to have anti-apoptotic functions[8] and lies downstream of p53 [9], similar to what we and others have described for p21. [10-12].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The Hsp27 protein, which lies downstream of p38MAPK, is a member of the heat-shock class of proteins which play pivotal roles in a variety of cellular processes such as stress and apoptosis. Hsp27 is of particular interest to our laboratory because it has been described to have anti-apoptotic functions[8] and lies downstream of p53 [9], similar to what we and others have described for p21. [10-12].…”
Section: Resultsmentioning
confidence: 79%
“…Using proteomic and then immunoblotting analysis in RCC, we have confirmed that phospho (but not native) Hsp27 is elevated in ccRCC in a parallel manner to p21. These findings were of special interest, since both proteins are induced by p53 [9], and there are reports that elevated levels of Hsp27[20], as p21[5], are associated with decreased patient survival. These data are also consistent with our pathway analysis showing that the p53 pathway is altered in ccRCC (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Although HSF-1 is considered to be the transcription factor responsible for Hsp27 induction, other factors can also induce Hsp27 (54). For example, wild type p53, a proapoptotic protein, was reported to induce Hsp27 expression in prostate cancer cells but not by mutant p53.…”
Section: Discussionmentioning
confidence: 99%
“…1B). These two polypeptides were identified as the p53-inducible gene products 14-3-3 (27) and HSP27 (28) (Table I), and their downregulation in Barrett's epithelium suggests that p53 may be attenuated as a transcription factor. Other proteins of interest identified by this method include galectin-7, annexin-1, and calgranulin A (Table II).…”
Section: Identification Of a Novel Polypeptide Overproduced In Barretmentioning
confidence: 99%